Electrocardiographic Changes in Amitriptyline Poisoning - Barnes, R. J. (1968)
In imipramine and amitriptyline poisoning the electrocardiographic abnormalities comprise arrhythmias, widening of the QRS complex, and marked changes in die S–T segment. These features were found to be of value in the differential diagnosis of unknown poisoning. The unusual configuration of qR with raised S–T segment in V1, simulating myocardial infarction, was seen in one of our patients and has been noted in four cases reported by other workers.